Human Immunodeficiency Virus infection associated with crack cocaine use: the impact on perinatal transmission among 890 pregnancies in Brazil - Carvalho, Newton Sergio de; Berti, Camila Cristi Vieira; Rauen, Jordana; Medeiros, Adeli Regina Prizybicien; Maffini, Cibele Feroldi; Tristão, Edson Gomes; Sbalqueiro, Renato Luiz (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Human Immunodeficiency Virus infection is a prevalent infection occurring during pregnancy. The implementation of a program to screen and prevent vertical transmission is highly important in Public Healthcare. Pregnant crack users could face difficulties to test and adhere to the Highly Active Antiretroviral Therapy. Objective: The purpose of this research paper was to investigate whether crack cocaine abuse increases Human Immunodeficiency Virus perinatal transmission rates, as well as to evaluate the risk factors associated with such an increase. Methods: Design: A retrospective study. Setting: Department of Obstetrics and Gynecology, General Hospital of Universidade Federal do Paraná. Population: pregnancies of Human Immunodeficiency Virus-positive women who were using crack cocaine (n=64) were compared with that of non-users (n=826) from 2005 to 2013. Prenatal medical records, delivery records, and newborn records were analyzed. Main Outcome Measures: The vertical transmission of Human Immunodeficiency Virus in the group of crack cocaine users was 9.37% (6) versus 2.54% (21) among non-users (p=0.009744). Results: Over the years of the study, there was a decrease in the vertical transmission rate in non-users, while this number remained constant in the group of users. When analyzing the cases of perinatal transmission, it was found that 83.34% (5) had inadequate prenatal care, and 100% (6) had inadequate Human Immunodeficiency Virus treatment, compared to the group in which there was no vertical transmission, where 65.52% (38) had inadequate prenatal care and 70.86% (41) had inadequate treatment. Conclusion: Vertical transmission is higher among crack cocaine users and did not decrease over the years of the study, as occurred among non-users. Trends that explain this increase were non-adherence to adequate prenatal care, Human Immunodeficiency Virus diagnosis during pregnancy, irregular treatment, absence of intrapartum antiretroviral prophylaxis, and vaginal delivery route.